Cyclic AMP, Protein Kinase A, and Phosphodiesterases: Proceedings of an International Workshop - Stratakis, C. A. (Hormone and Metabolic Research, 2012)
Cyclic nucleotides cAMP and cGMP are part of almost all major cellular signaling pathways. Phosphodiesterases (PDEs) are enzymes that regulate the intracellular levels of cAMP and cGMP. Protein kinase A or cAMP-dependent protein kinase mediates most cAMP effects in the cell. Over the last 25 years, various components of this group of molecules have been involved in human diseases, both genetic and acquired. Lately, the PDEs attract more attention. The pharmacological exploitation of the PDE’s ability to regulate cGMP and cAMP, and through them, a variety of signaling pathways, has led to a number of new drugs for diverse applications from the treatment of erectile dysfunction to heart failure, asthma, and chronic obstructive pulmonary disease. We present the abstracts (available online) and selected articles from the proceedings of a meeting that took place at the National Institutes of Health (NIH), Bethesda, MD, June 8–10, 2011.